2014
DOI: 10.1002/oby.20702
|View full text |Cite
|
Sign up to set email alerts
|

BMI and the risk of colorectal adenoma in African‐Americans

Abstract: Objectives Obesity is associated with the activation of the molecular pathways that increase the risk of colorectal cancer. Increasing body mass index may accelerate the development of adenomatous polyps, the antecedent lesion of colorectal cancer. The aim of this study was to assess the BMI effect on the risk of colonic polyp and adenoma in African American. Design and Methods We examined the records of 923 patients who underwent colonoscopy. Demographic and clinical data were collected before colonoscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
(65 reference statements)
1
27
0
1
Order By: Relevance
“…Obesity has been strongly associated with precancerous lesions and conditions such as colon adenomas [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], monoclonal gammopathy [87][88][89][90][91][92][93][94][95][96][97][98], chronic pancreatitis [99][100][101][102], or inflammatory bowel disease (IBD) [103][104][105][106]. Observed risks of cancers associated with obesity include breast [107][108][109][110][111], colorectal [112][113][114][115], pancreatic [99]…”
Section: Morbid Obesitymentioning
confidence: 99%
“…Obesity has been strongly associated with precancerous lesions and conditions such as colon adenomas [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], monoclonal gammopathy [87][88][89][90][91][92][93][94][95][96][97][98], chronic pancreatitis [99][100][101][102], or inflammatory bowel disease (IBD) [103][104][105][106]. Observed risks of cancers associated with obesity include breast [107][108][109][110][111], colorectal [112][113][114][115], pancreatic [99]…”
Section: Morbid Obesitymentioning
confidence: 99%
“…Epidemiological data indicate that the risk of colon cancer is strongly associated with increasing body mass index (BMI) [110]. Similar to smoking and a history of colon polyps, a BMI value >25 also significantly increases the risk of colon cancer [111]. In addition to human data, several rodent models have been utilized to demonstrate a link between obesity and increased colon cancer.…”
Section: Link Between Obesity and Colon Cancermentioning
confidence: 99%
“…Obesity is associated with the activation of insulin-like growth factor (IGF), oxidative stress and inflammatory pathways that increase the risk of adenoma and CRC [24, 25]. Ochs-Balcom et al [25] reported statistically significant association of IGF-1 with colorectal adenoma among African Americans.…”
Section: Introductionmentioning
confidence: 99%